Glucosinolates of Sisymbrium officinale and S. orientale - Azra Đulović; Marijana Popović; Franko Burčul; Vedrana Čikeš Čulić; Sandra Marijan; Mirko Ruščić; Nikolina Anđelković; Ivica Blažević (Molecules, 2022)
Glucosinolates (GSLs) from Sysimbrium officinale and S. orientale were analyzed qualitatively and quantitatively by their desulfo-counterparts using UHPLC-DAD-MS/MS. Eight GSLs were identified in S. officinale, including Val-derived (glucoputranjivin) and Trp-derived (4-hydroxyglucobrassicin, glucobrassicin, 4-methoxyglucobrassicin, and neoglucobrassicin) as the major ones followed by Leu-derived (Isobutyl GSL), Ile-derived (glucocochlearin) and Phe/Tyr-derived (glucosinalbin). Different S. orientale plant parts contained six GSLs, with Met-derived (progoitrin, epiprogoitrin, and gluconapin) and homoPhe-derived (gluconasturtiin) as the major ones, followed by glucosinalbin and neoglucobrassicin. GSL breakdown products obtained by hydrodistillation (HD) and microwave-assisted distillation from S. officinale, as well as isopropyl isothiocyanate, as the major volatile in both isolates, were tested for their cytotoxic activity using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Generally, all volatile isolates showed similar activity toward the three cancer cell lines. The best activity was shown by isopropyl isothiocyanate at a concentration of 100 µg/mL after 72 h of incubation, with 53.18% for MDA-MB-231, 56.61% for A549, and 60.02% for the T24 cell line.